A parallel implementation of the LTSn method for a radiative transfer problem - Souto, R. P.; Velho, H. F. de Campos; Stephany, S.; Preto, A. J.; Segatto, C. F.; Vilhena, M. T. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
A radiative transfer solver that implements the LTSn method was optimized and parallelized using the MPI message passing communication library. Timing and profiling information was obtained for the sequential code in order to identify performance bottlenecks. Performance tests were executed in a distributed memory parallel machine, a multicomputer based on IA-32 architecture. The radiative transfer equation was solved for a cloud test case to evaluate the parallel performance of the LTSn method. The LTSn code includes spatial discretization of the domain and Fourier decomposition of the radiances leading to independent azimuthal modes. This yields an independent radiative transfer equation for each mode that can be executed by a different processor in a parallel implementation. Speed-up results show that the parallel implementation is suitable for the used architecture.